Typical behavior development of Uruguayan housing Cooperatives constructions - Santilli, Adrián (2017)
Several national and international studies reveal that the housing access is one of the main problems that society is facing nowadays. Housing cooperatives constructions emerge as an alternative to satisfy low income social classes housing demand. Despite being a sustainable solution over time an in-depth study of the process shows several delays in the construction stage. This article shows a statistical study for the  characterization and determination of the Uruguayan cooperative construction behavior. This study allows knowing the typical behavior and the delays behavior, thus providing the managers a tool for the construction control. A database of 90 construction projects of housing cooperatives in Uruguay is taken into account for the accomplishment of a Cluster analysis that results in 4 standard behaviors of the cooperatives constructions.